PARTISIPASI ANGGARAN DAN KINERJA MANAJERIAL DENGAN KECUKUPAN ANGGARAN DAN JOB-RELEVANT INFORMATION SEBAGAI VARIABEL INTERVENING - Eko Budi Santoso; Tommi Adrian Hartanto (Fakultas Bisnis UKDW, 2012)
The aims of this study is to examine the budgetary participation and performance relationship in public sector organization. This research also attempts to examine whether budget adequacy and job-relevant information mediate the budgetary participation and performance relationship.Questionnaires data is collected using mail survey method. From 53 questionnaires were given to chief leveled as managers in Duta Wacana Christian University, questionnaires with complete answer were 50 questionnaires (94, 33%). A path analysis was utilized to examine the direct and indirect effects of budgetary participation on managerialperformance.The result of these study shows that the influence of between budget participation toward managerial performance through job-relevant information is higher than the direct influence of budget participation toward managerial performance. Budgetary participation also directly influence budget adequacy and job-relevant information. However, budgetary participation did not affect managerial performance via the intervening variables of budget adequacy.Keywords: budget participation, managerial performance, budget adequacy, hob-relevant information